Insightful Exchange With ChatGPT on Hyperthyroidism - Ali, Sara Mohamed (Scripta Medica, 2024)
Embracing innovative solutions is crucial for navigating modern healthcare complexities. Platforms such as ChatGPT represent progress toward this aim. By leveraging AI, we empower patients, improve healthcare outcomes and enhance lives. Ongoing research and refinement are imperative for unlocking ChatGPT’s full potential.